Local and Global Praise Strategy - Khalis Kohari (CV. Syntax Corporation Indonesia, 2023)
The study was put forward by Prof. Dr. Hj. Tutty Alawiyah, USA, In this study, he explained the importance of combining da'wah strategies that focus on the local context with those that focus on the global context in spreading Islamic da'wah. He also highlighted how important a good understanding of the social, cultural, and political context is in developing an effective da'wah strategy. This study provides an interesting view of how to spread Islamic da'wah in the current era of globalization in ways that are appropriate to local and global contexts. This study also highlights the importance of understanding local communities' views of life and values when developing da'wah strategies. He stated that da'wah strategies that do not pay attention to the views of life and local community values will be less effective in spreading da'wah. This study also highlights the importance of inter-religious cooperation in spreading Islamic da'wah. He stated that cooperation between religious communities could help reach a wider audience and reduce tensions between religious communities. Is the method used in qualitative methodology helpful in understanding more deeply the social, cultural, and political context in developing effective da'wah strategies, as well as the views of life and local community values that need to be considered in spreading Islamic da'wah? In addition, the qualitative methodology can also assist in identifying the potential for cooperation between religious communities in spreading Islamic da'wah. Overall, this study provides an interesting view of how to spread Islamic da'wah in the current era of globalization in a way appropriate to the local and global context, taking into account the views of life and values of local communities and local cooperation between religious communities.